2018
DOI: 10.1002/cpt.1116
|View full text |Cite
|
Sign up to set email alerts
|

Common Polymorphisms of CYP2B6 Influence Stereoselective Bupropion Disposition

Abstract: Bupropion hydroxylation is a bioactivation and metabolic pathway, and the standard clinical CYP2B6 probe. This investigation determined the influence of CYP2B6 allelic variants on clinical concentrations and metabolism of bupropion enantiomers. Secondary objectives evaluated the influence of CYP2C19 and P450 oxidoreductase variants. Healthy volunteers in specific cohorts (CYP2B6*1/*1, CYP2B6*1/*6, CYP2B6*6/*6, and also CYP2B6*4 carriers) received single-dose oral bupropion. Plasma and urine bupropion and hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 50 publications
2
29
0
Order By: Relevance
“…In vitro-in vivo concordance is less consistent for CYP2B6*4 than for decreased metabolism polymorphisms, which may be influenced by the rarity of CYP2B6*4. CYP2B6.4 had minimally increased bupropion hydroxylation in vitro, and numerically but not significantly higher plasma hydroxybupropion/bupropion AUC ratios in CYP2B6*4 hererozygotes for the racemate (Kirchheiner et al, 2003;Zhu et al, 2012;Ma et al, 2018;Kharasch and Crafford, 2019) and enantiomers (Kharasch and Crafford, 2019). Based on these patterns, and the present in vitro results, it could be expected that other CYP2B6 polymorphisms coding for diminished (*5, *6, *7, *9, *19, *26) or defective (*16) in vitro bupropion hydroxylation might result in diminished in vivo bupropion hydroxylation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro-in vivo concordance is less consistent for CYP2B6*4 than for decreased metabolism polymorphisms, which may be influenced by the rarity of CYP2B6*4. CYP2B6.4 had minimally increased bupropion hydroxylation in vitro, and numerically but not significantly higher plasma hydroxybupropion/bupropion AUC ratios in CYP2B6*4 hererozygotes for the racemate (Kirchheiner et al, 2003;Zhu et al, 2012;Ma et al, 2018;Kharasch and Crafford, 2019) and enantiomers (Kharasch and Crafford, 2019). Based on these patterns, and the present in vitro results, it could be expected that other CYP2B6 polymorphisms coding for diminished (*5, *6, *7, *9, *19, *26) or defective (*16) in vitro bupropion hydroxylation might result in diminished in vivo bupropion hydroxylation.…”
Section: Discussionmentioning
confidence: 99%
“…There is high concordance between POR and CYP2B6 genetic variant effects on bupropion metabolism in vitro and in vivo. POR*28 had little effect on bupropion hydroxylation in vitro, or in vivo, based on plasma hydroxybupropion/bupropion area under the curve (AUC) ratios and urine hydroxybupropion formation clearance (Gao et al, 2016;Lv et al, 2016;Kharasch and Crafford, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Bupropion metabolism is stereoselective in vitro, [16][17][18] and single-dose studies in healthy volunteers have shown that it is stereoselective in vivo. [19][20][21][22][23][24] Plasma exposures are 2-fold to 6-fold higher for R-bupropion than S-bupropion, S-bupropion apparent oral clearance exceeds that of R-bupropion, and R,R-hydroxybupropion exposures are 20-fold to 65-fold higher than S,S-hydroxybupropion. 20,21,24,25 Stereoselective disposition is important, because bupropion antidepressant and antismoking effects are attributed to S,S-hydroxybupropion rather than R,Rhydroxybupropion, despite the lower plasma concentrations.…”
mentioning
confidence: 99%
“…[19][20][21][22][23][24] Plasma exposures are 2-fold to 6-fold higher for R-bupropion than S-bupropion, S-bupropion apparent oral clearance exceeds that of R-bupropion, and R,R-hydroxybupropion exposures are 20-fold to 65-fold higher than S,S-hydroxybupropion. 20,21,24,25 Stereoselective disposition is important, because bupropion antidepressant and antismoking effects are attributed to S,S-hydroxybupropion rather than R,Rhydroxybupropion, despite the lower plasma concentrations. [26][27][28][29] Although the vast majority of studies have traditionally evaluated plasma concentrations of racemic hydroxybupropion, Figure 1 Bupropion metabolism.…”
mentioning
confidence: 99%